2019
DOI: 10.1108/jfm-11-2017-0058
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance prioritization – a review on factors and methods

Abstract: Purpose Maintenance is a compulsory cost in any asset's operation and requires sufficient budget to be supported. However, insufficient maintenance allocation would lead to maintenance prioritization being practiced as a solution to relief the maintenance demands. The purpose of this paper is to review and discuss the related literature on the factors considered and methods practiced in maintenance prioritization, especially in asset managements. Design/methodology/approach A thorough literature search relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 95 publications
0
23
0
Order By: Relevance
“…This is because participants cannot cope without these spaces/services or that these spaces/services affect their performance. Chong et al (2019) actually clarified that these services are generally the most essential and should always be accorded first priority. Similarly, Orr et al (2011) indicated that the setting of a student accommodation should make students see studying as their main occupation.…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because participants cannot cope without these spaces/services or that these spaces/services affect their performance. Chong et al (2019) actually clarified that these services are generally the most essential and should always be accorded first priority. Similarly, Orr et al (2011) indicated that the setting of a student accommodation should make students see studying as their main occupation.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Similar to the spaces, it is evident from the proceeding that the living and learning related services are those that students perceive as more important. In buttress, Chong et al (2019) clarified that services which are health, safety, security and environment related are generally the most essential and should always be accorded first priority. Thus, the living related services could further be classified as health and environment, security and safety, and building services and maintenance related.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this study, owners reported a high level of satisfaction with their tanks, which was evidenced by the frequency of maintenance actions that were undertaken; the number of tank systems which had been repaired and the number of owners making positive alterations to their tank system. The perceived value of an asset is important, since given resourcing constraints, maintenance is typically prioritised towards assets of highest perceived value or where inaction will lead to significant repercussions (Chong et al 2019). Indeed, Gardiner (2009) postulated that owners who did not value their tanks highly would be more likely to stop using them when faults arose.…”
Section: Value Of the Tank Systemmentioning
confidence: 99%
“…▪ Technical factors: specified as the specialized variables employments markers to watch the execution of a specific framework, Handle, maintenance, and components (Chong et al, 2019). ▪ Financial factors: Monetary components are made up of two primary components which are the accessible budget and the required taken a toll.…”
Section: Organizational Factormentioning
confidence: 99%